2023
DOI: 10.3390/pharmaceutics15030837
|View full text |Cite
|
Sign up to set email alerts
|

Nanocarriers for the Delivery of Neuroprotective Agents in the Treatment of Ocular Neurodegenerative Diseases

Abstract: Retinal neurodegeneration is considered an early event in the pathogenesis of several ocular diseases, such as diabetic retinopathy, age-related macular degeneration, and glaucoma. At present, there is no definitive treatment to prevent the progression or reversal of vision loss caused by photoreceptor degeneration and the death of retinal ganglion cells. Neuroprotective approaches are being developed to increase the life expectancy of neurons by maintaining their shape/function and thus prevent the loss of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 226 publications
0
4
0
Order By: Relevance
“…Nanocarriers may become a useful tool to deliver drugs intra-ocularly with limited invasive technology to minimize the burden for patients. 102 We discuss in the next chapters whether local administration in the eye of inhibitors of ATP synthesis via glycolysis and/or OXPHOS may be a realistic therapeutic approach.…”
Section: Physiological and Pathological Angiogenesismentioning
confidence: 99%
“…Nanocarriers may become a useful tool to deliver drugs intra-ocularly with limited invasive technology to minimize the burden for patients. 102 We discuss in the next chapters whether local administration in the eye of inhibitors of ATP synthesis via glycolysis and/or OXPHOS may be a realistic therapeutic approach.…”
Section: Physiological and Pathological Angiogenesismentioning
confidence: 99%
“…In addition to the hydrophobic interactions and electrostatic, charge transfer interactions and hydrogen bonding may also contribute to the binding activities [ 22 ]. Several lines of evidence have shown that melanin can interact with drug molecules and influence their distribution in the posterior segment of the eye [ 23 ].…”
Section: Biological Barriers To Ocular Drug Deliverymentioning
confidence: 99%
“… Barriers to ocular drug delivery along with routes of ocular drug delivery. Reproduced with permission from Patel C et al, 132 CC BY 4.0. …”
Section: Strategies To Enhance the Ocular Bioavailability Of Proteins...mentioning
confidence: 99%